Log your car: The non-invasive vehicle forensics - Mansor, Hafizah; Markantonakis, Konstantinos; Akram, Raja Naeem; Mayes, Keith; Gurulian, Iakovos; , (IEEE, 2016)
Digital forensics is becoming an important feature for many embedded devices. In automotive systems, digital forensics involves multiple electronic control units (ECUs) used to support the connected and intelligent vehicle’s technology. Digital evidence from these ECUs can be used in forensics investigation and analysis. Such a mechanism can potentially facilitate crash investigation, insurance claims and crime investigation. Issues related to forensics include the authenticity, integrity and privacy of the data. In this paper, the security of the forensic process and data in automotive systems is analysed. We propose an efficient, secure, privacy-preserving and reliable mechanism to provide a forensics data collection and storage process. A diagnostic application for smart phones, DiaLOG, is incorporated in the proposed process that uses a secure protocol to communicate the collected forensic data to a secure cloud storage. The proposed protocol for communicating forensic data is implemented to measure performance results and formally analysed using Scyther and CasperFDR with no known attack found.